Indonesian Capital Market Reaction to Simultaneous Elections in 2024 - Putra, Pande Gede Bagus Armana; Sukartha, P. Dyan Yaniartha (E-Jurnal Akuntansi; Vol 34 No 12 (2024), 2024)
This study aims to analyze the reaction of the Indonesian capital market to the simultaneous general election event in 2024. Measurements were made on 764 company samples. The measurement aspect uses abnormal return and cumulative abnormal return. Through the analysis method used includes descriptive statistical test, one sample t-test, and paired t-test. The test results on the first hypothesis show a significant abnormal return on the first day and the third day after the simultaneous general election in 2024 and on the second hypothesis show a significant cumulative abnormal return difference between before and after the simultaneous general election in 2024. The test results show that the 2024 simultaneous general election event has information content that forms a reaction to the Indonesian capital market.